KERJA SAMA PERTAHANAN INDONESIA – AMERIKA SERIKAT MELALUI PROGRAM FOREIGN MILITARY SALES (FMS) - Afrian Hidayat; Mhd. Saeri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
Diplomatic relations between Indonesia and the US in the field of defense have been very volatile for a long time, both the closeness and depth of defense cooperation. Bilateral defense cooperation is carried out in the context of improving relations between the military and to increase the professionalism of the TNI and achieving the objectives of the Indonesian state defense such as maintaining national sovereignty and integrity. Indonesia's interest in establishing defense cooperation with the US is because most of the main weapons systems (alutsista) tools come from the US with the Foreign Military Sales (FMS) program which aims to build a modern military.This study uses qualitative methods with data from library sources and secondary sources such as books, papers and materials from other open sources. This study uses the Liberalism Perspective, Level of Analysis of nation-states, and International Cooperation Theory.The results of this study are that the Foreign Military Sales (FMS) Program has had a significant impact on increasing Indonesia's security capacity in the fields of terrorism prevention, maritime security, and increasing world peacekeeping operations personnel through purchasing defense equipment, increasing TNI professionals, and increasing military budgets. Defense cooperation between Indonesia and the US will be largely determined by regional security dynamics so Indonesia must develop innovative ideas in the regional area by involving large countries such as the United States. Keywords: Foreign Military Sales (FMS), Defense Diplomacy, Defense Cooperation